2017
DOI: 10.1159/000479741
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Retinal Pigment Epithelial Hyperplasia and Glial Proliferation Masquerading as Progressive Recurrent Retinoblastoma: A Case Report Review and Clinicopathologic Correlation

Abstract: Background: Recurrences of retinoblastoma tumors, particularly scar recurrences, are a common phenomenon in the management of this cancer. Consolidative treatment with laser and cryotherapy are required for local control of disease. It is known that consolidative therapy can induce retinal pigment epithelium (RPE) hyperplasia and gliosis. Herein we report extensive RPE hyperplasia and gliosis during laser therapy for a focal scar recurrence, which presented as a progressive retinal opacification mimicking acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…RPE alterations and other adverse events, including RPE hyperplasia, gliosis, and mottling, have been previously documented in the eyes of some Rb patients treated with Melphalan and Topotecan [7,9,14]. [14] were the rst to report cytotoxicity of Melphalan, Topotecan, and carboplatin on RPE cells.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…RPE alterations and other adverse events, including RPE hyperplasia, gliosis, and mottling, have been previously documented in the eyes of some Rb patients treated with Melphalan and Topotecan [7,9,14]. [14] were the rst to report cytotoxicity of Melphalan, Topotecan, and carboplatin on RPE cells.…”
Section: Discussionmentioning
confidence: 95%
“…The retinal pigment epithelium (RPE) is a pigmented cell monolayer responsible for transporting metabolic end products from the subretinal space to the blood and recycling photoreceptor outer disks for the maintenance of visual cells [6]. RPE hyperplasia, gliosis, mottling, and other alterations on ultimate visual acuity can manifest following chemotherapy in Rb patients [7][8][9]. As the RPE is vital for the health and function of the neural retina, any failure of any RPE functions can lead to retinal degeneration, loss of visual function, and blindness [10].…”
Section: Introductionmentioning
confidence: 99%
“…Aziz et al [11] recently reported 2 cases of hemorrhagic retinopathy, though these occurred only 1 week after a second intravitreal melphalan injection. Systemic chemotherapy with laser consolidation has also been reported to result in glial proliferation [12]. In this case, our patient was treated with all of the above therapies: systemic chemotherapy with laser consolidation, salvage IAC, and intravitreal melphalan.…”
Section: Discussionmentioning
confidence: 98%
“…temic chemotherapy with laser consolidation has also been reported to result in glial proliferation [12]. In this case, our patient was treated with all of the above therapies: systemic chemotherapy with laser consolidation, salvage IAC, and intravitreal melphalan.…”
mentioning
confidence: 94%